ONLINE ADVERTISING IN THE TOURISM INDUSTRY AND ITS IMPACT ON CONSUMERS - JULIANE SAß (Tourism & Management Studies)
The study depicts the various tools of online advertising and their effects on customers, in particular tourists to the Algarve region in Portugal. The purpose of this study is to find out about the degree of Internet usage of travelers and tourists as well as their preferences in online advertising. Furthermore, modern online marketing methods are researched and compared in order to find the most successful ones. Current trends and most effective online advertising methods are researched through secondary literature, a personal interview with the marketing & sales manager of the ROBINSON Club Quinta da Ria in Portugal and a survey. Altogether 248 tourists were questioned at Faro airport in Portugal. Through the investigation it is found that the majority of tourists to the Algarve region uses and prefers the Internet as a medium to gain travel relevant information and to book a holiday. The literature review describes all components of online advertising such as Search Marketing, interactive advertising, online public relations, viral marketing, opt-in email marketing and online partnerships. Out of these methods, Search Marketing, especially sponsored listings, generate rejection, if compared to organic ranking results. Furthermore, tourists have negative attitudes towards banner and pop-up advertising and consider them as Spam. Optin E-mail marketing on the other hand generates positive perceptions and as a result is one of the most successful online marketing methods. The use of social media represents a very effective, widely spread and well-liked communication and advertising tool. In general, tourists have more negative attitudes towards advertising on the Internet.